Relationship between use of desmopressin in male patients with lower urinary tract symptoms and occurrence of hyponatremia: A nationwide population-based study using the National Health Insurance Service database - Jeon, Byeong Jo; Tae, Bum Sik; Park, Jae Young; Bae, Jae Hyun (Investigative and clinical urology, 2025)
Desmopressin, frequently prescribed for nocturia, is associated with an elevated risk of hyponatremia. This study examined the incidence and risk factors of hyponatremia in male patients with benign prostatic hyperplasia using nationwide Korean health data. From the National Health Insurance Service database, we analyzed data on desmopressin and hyponatremia in Korean adults with benign prostatic hyperplasia between 2011 and 2012. The patients were followed-up until December 2020. We tested the effects of desmopressin on hyponatremia risk using propensity score-matched Cox regression models and Kaplan-Meier survival analysis. Among 33,533 patients, the incidence of hyponatremia was 6.0%, 4.5%, and 5.0% in the desmopressin, alpha-blocker, and combination therapy groups, respectively. After propensity score matching, desmopressin use was not significantly associated with an increased risk of hyponatremia (hazard ratio 1.273, 95% confidence interval 0.988-1.640; p=0.062). Significant predictors of hyponatremia included advanced age, chronic heart failure, peripheral vascular disease, and renal disease. Desmopressin prescription following careful patient selection and regular monitoring does not significantly increase the risk of hyponatremia compared to other lower urinary tract symptom treatments. Therefore, it remains a viable and effective option for managing nocturia, particularly in patients with nocturnal polyuria. However, clinicians should implement routine monitoring protocols, including serum sodium checks, particularly in high-risk populations, to ensure the safe and effective use of desmopressin.